Exploring teachers’ perceptions of their readiness to support learners with barriers to learning in the full-service classroom - Claassen, Sandra Petronella (University of the Free State, 2024)
Following the Salamanca Conference held in Spain in June 1994, which placed a priority on individuals with disabilities, South Africa affirmed its dedication to inclusive education by releasing Education White Paper 6. One of the core strategies outlined in Education White Paper 6 for implementing inclusive education in South African schools is the establishment of full-service schools. Full-service schools provide support to learners with a wide range of learning needs. As a result of a range of factors that could lead to barriers to learning and development, the teacher needs to employ adaptive teaching techniques, tailored curricula and streamlined assessment methods. Ensuring that teachers possess the necessary skills and resources for this task is of utmost importance. Nevertheless, teachers find themselves grappling with challenges within the full-service school environment, which in turn shapes their perceptions of their readiness to assist learners facing learning barriers. Moreover, the available support structures for teachers, particularly in rural regions, often prove to be either lacking or ineffectual. Drawing from the ecological systems theory proposed by Bronfenbrenner, this study adopted an interpretivist paradigm to conduct qualitative semi-structured interviews with teachers at full-service schools within the Motheo rural district in South Africa. Thematic analysis was employed to determine teachers’ perceptions, challenges and sense of preparedness in supporting learners within the full-service school context. The three main themes that surfaced were directly aligned with the three secondary research questions: 1) barriers experienced by teachers, 2) resources accessible to teachers in the rural full-service school, and 3) assistance required by teachers in the full-service school. Sub-themes emerged from the collected data. Recommendations are made to the Department of Education, school management teams and school governing bodies to address the findings in relation to the themes and sub-themes that emerged from the study. The study bears value because it highlights the challenges teachers experience, which support structures are available to them and which support structures are still necessary for teachers in FSSs in rural areas. This information may assist the DoE to understand the challenges teachers experience and to render the appropriate support needed.
Dissertation (M.Ed.(Education))--University of the Free State, 2024
Keywords: Inclusive education; Full-service schools; Teacher perceptions; Challenges; Support structures; Bronfenbrenner’s ecological systems theory; Thematic analysis